Rupturing the Surface: Performance as Opposition in Ocaña: retrat intermitent (Ventura Pons, 1978). - Tahmassian, Lena (Bulletin of Hispanic Studies (1475-3839), 2019)
This article takes a new look at one of the most notable films of the era of Spain's Transition to democracy: Ventura Pons' directorial debut, Ocaña: retrat intermitent (1978). Screened during a time characterized by an explosion of freedoms, but also by the depoliticization of politics and of Spain's recent historical conflicts, the documentary's uncanniness can be explored productively as a work that resists the reduction of politics to individual identity. An analysis at the intersection of queer theory and avant-garde praxis suggests that Pons' portrait of the countercultural and gender-bending performer offers a way out of what would become the political impasse of hegemonic postmodernism. This revision contributes to the critical dialogue on the Transition's countercultural production as the latter becomes loaded with increased relevance through attempts to understand Spain's current political upheavals.